The differentiated approach in forming swimming abilities and skills of students - Nikolskiy A.U (Kharkov National Pedagogical University, 2010)
It is considered the directions of organization and methods of conducting of lessons with students. In experiment took part students of the 17-20 years old. The criteria of forming of typological educational groups are presented on the initial stage of teaching swimming of students. The degree of connection of the hereditarily conditioned swimming coordinating inclination is certain with the indexes of formed swimming abilities and skills of students. It is well-proven that a process of capture motive habits is under unreserved influence of conservative heredity of individual.